Soft magnetic metal strip, magnetic core and magnetic component
Patent Information
- Application Number
- CN202610544571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-01-26
- Filing Date
- 2026-04-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]用于解决技术问题的技术方案
Smart Images

Figure CN122991791A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a soft magnetic metal strip, a magnetic core, and a magnetic component. Background Technology
[0002] In recent years, in order to make magnetic cores more efficient, smaller and lighter, the magnetic materials used have been required to have lower coercivity and higher permeability.
[0003] Patent Document 1 describes an invention concerning Fe-based amorphous alloy thin strips, etc. By having a plurality of laser irradiation mark rows consisting of multiple laser irradiation marks on at least one side of the thin strip, iron loss can be reduced and the rise of excitation power can be suppressed.
[0004] Patent Document 2 discloses an invention regarding a method for manufacturing a microcrystalline soft magnetic alloy. Patent Document 2 discloses a nanocrystalline heat treatment method, which involves winding an amorphous alloy strip around a core, performing a first heat treatment at a temperature lower than the crystallization initiation temperature to alleviate stress within the strip, removing the core, and then performing a second heat treatment at a temperature higher than the crystallization initiation temperature. This method can suppress the reduction in magnetic properties caused by stress generated during heat treatment.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent No. 6687168
[0008] Patent Document 2: Japanese Patent Application Publication No. 1-247557 Summary of the Invention
[0009] Technical solutions for solving technical problems
[0010] To achieve the above objectives, the soft magnetic metal strip according to the first aspect of the present invention has a compositional formula (Fe 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The main components of the soft magnetic metal ribbon are shown in the (atomic ratio) diagram.
[0011] X1 is selected from one or more of Co and Ni.
[0012] X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements.
[0013] M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V.
[0014] The following conditions must be met: 0 ≤ a ≤ 0.100, 0.020 ≤ b ≤ 0.200, 0 ≤ c ≤ 0.100, 0 ≤ d < 0.160, 0 ≤ e ≤ 0.030, 0 ≤ f ≤ 0.030, and 0 ≤ p ≤ 0.500.
[0015] The aforementioned soft magnetic metal ribbon comprises amorphous and crystalline portions.
[0016] When the angle of one peak selected from the X-ray diffraction peaks originating from the crystallization in the first plane of the aforementioned soft magnetic metal ribbon is set to 2θ1, and the crystal plane indices are set to (h1, k1, l1),
[0017] It satisfies 60.00°≤2θ1≤66.00°.
[0018] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization in the second plane located opposite to the first plane of the aforementioned soft magnetic metal ribbon is set to 2θ2, and the crystal plane indices are set to (h2, k2, l2),
[0019] It satisfies 60.00°≤2θ²≤66.00°.
[0020] Let it be 2θ1-2θ2=Δθ 12 hour,
[0021] Satisfying 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
[0022] The second aspect of the present invention relates to a magnetic core having a wound portion with a soft magnetic metal strip wound around it, the soft magnetic metal strip having a compositional formula (Fe 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The principal components are shown in the (atomic ratio)
[0023] X1 is selected from one or more of Co and Ni.
[0024] X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements.
[0025] M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V.
[0026] The following conditions must be met: 0 ≤ a ≤ 0.100, 0.020 ≤ b ≤ 0.200, 0 ≤ c ≤ 0.100, 0 ≤ d < 0.160, 0 ≤ e ≤ 0.030, 0 ≤ f ≤ 0.030, and 0 ≤ p ≤ 0.500.
[0027] The aforementioned winding portion includes an amorphous portion and a crystalline portion.
[0028] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the outer surface of the soft magnetic metal ribbon located on the outermost surface of the aforementioned winding portion is set to 2θ3, and the crystal plane indices are set to (h3, k3, l3),
[0029] It satisfies 60.00°≤2θ3≤66.00°.
[0030] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the inner surface of the soft magnetic metal strip located on the innermost surface of the aforementioned winding portion is set to 2θ4, and the crystal plane indices are set to (h4, k4, l4),
[0031] It satisfies 60.00°≤2θ4≤66.00°.
[0032] Let it be 2θ3-2θ4=Δθ 34 hour,
[0033] Satisfying 0.00° < |Δθ 34 | ≤4.90° and (h3, k3, l3) = (h4, k4, l4). Attached Figure Description
[0034] Figure 1 This is a schematic diagram of a magnetic core according to one embodiment of the present invention.
[0035] Figure 2 This is a schematic diagram of a magnetic core according to one embodiment of the present invention.
[0036] Figure 3 This is a schematic diagram of a magnetic core according to one embodiment of the present invention.
[0037] Figure 4 This is a schematic diagram of the single-roller process.
[0038] Explanation of reference numerals in the attached figures
[0039] 1…Magnetic core (wound core, laminated core); 11…Outermost surface; 13…Innermost surface; 31…Nozzle; 32…Molten metal; 33…Roller; 34…Soft magnetic metal strip; 34a…Free surface; 34b…Roller surface; 35:Cavity. Detailed Implementation
[0040] The purpose of this invention is to provide a soft magnetic metal strip and magnetic core with low coercivity and high permeability.
[0041] The soft magnetic metal strip involved in the first aspect of the present invention can also satisfy 0≤d≤0.150.
[0042] The soft magnetic metal strips involved in the first aspect of the present invention can also have Fe-based nanocrystals with an average crystal grain size of less than 50.0 nm.
[0043] The first aspect of the present invention relates to a magnetic core having a wound portion on which the aforementioned soft magnetic metal strip is wound.
[0044] Other magnetic cores according to the first aspect of the present invention have a stacked portion having the aforementioned soft magnetic metal strips.
[0045] The magnetic core involved in the second aspect of the present invention can also satisfy 0≤d≤0.150.
[0046] In the magnetic core according to the second aspect of the present invention, the soft magnetic metal strip may also include an amorphous portion and a crystalline portion.
[0047] Alternatively, by selecting one peak from the X-ray diffraction peaks originating from the crystallization in the first plane of the aforementioned soft magnetic metal ribbon and setting its angle as 2θ1, and setting the crystal plane indices as (h1, k1, l1), the following conditions are met: 60.00°≤2θ1≤66.00°.
[0048] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization in the second plane located opposite to the first plane of the aforementioned soft magnetic metal ribbon is set as 2θ2, and the crystal plane indices are set as (h2, k2, l2), the following conditions are met: 60.00°≤2θ2≤66.00°.
[0049] Let it be 2θ1-2θ2=Δθ 12 hour,
[0050] Satisfying 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
[0051] In the magnetic core according to the second aspect of the present invention, the shape of the winding portion may also be a shape having two or more curvature circles with different centers.
[0052] In the magnetic core according to the second aspect of the present invention, the radii of two or more of the above-mentioned curvature circles may also be smaller than the equivalent circle diameter of the hollow portion of the above-mentioned winding portion.
[0053] The magnetic component according to the first aspect of the present invention has the aforementioned soft magnetic metal strip.
[0054] The magnetic component according to the first or second aspect of the present invention has the magnetic core described above.
[0055] (First Implementation)
[0056] Hereinafter, a first embodiment of the present invention will be described based on the accompanying drawings. The present invention is not limited to any of the following first and second embodiments, and can be implemented with appropriate modifications within the scope of the invention's objectives. Furthermore, descriptions that are repeated are sometimes appropriately omitted, but this does not limit the essence of the invention.
[0057] The shape of the magnetic core involved in this embodiment is not particularly limited. For example, it can be... Figure 1 The toroidal magnetic core 1 is shown. Below, the distance... Figure 1 The surface furthest from the central axis of the annular shape is designated as the outermost surface 11, and the surface closest to the central axis of the annular shape is designated as the innermost surface 13.
[0058] There are no particular limitations on the outer diameter, inner diameter, and height of the magnetic core 1. For example, the outer diameter can be between 0.5 mm and 250 mm. The inner diameter can be between 0.2 mm and 200 mm. The height can be between 1.0 mm and 250 mm.
[0059] The type of magnetic core 1 involved in this embodiment is not particularly limited. For example, it can be a wound core 1 obtained by winding a thin strip of soft magnetic metal, or a laminated core 1 obtained by stacking thin strips of soft magnetic metal.
[0060] The soft magnetic metal strip involved in this embodiment has the composition formula (Fe) 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The main components of the soft magnetic metal ribbon are shown in the (atomic ratio) diagram.
[0061] X1 is selected from one or more of Co and Ni.
[0062] X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements.
[0063] M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V.
[0064] It satisfies 0≤a≤0.100, 0.020≤b≤0.200, 0≤c≤0.100, 0≤d<0.160, 0≤e≤0.030, 0≤f≤0.030, and 0≤p≤0.500.
[0065] There are no particular limitations on the specific methods used to determine the composition of soft magnetic alloy strips, i.e., the types of M, X1, and X2 mentioned above, and the values of a, b, c, d, e, f, and p mentioned above. For example, the composition of soft magnetic alloys can be specifically determined using scanning transmission electron microscopy (STEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), electron energy loss spectroscopy (EELS), fast Fourier transform (FFT) analysis of TEM images, powder X-ray diffraction (XRD), fluorescence X-ray spectroscopy (XRF), inductively coupled plasma atomic emission spectrometry (ICP-AES), infrared absorption spectroscopy, and thermal conductivity methods.
[0066] The components of the soft magnetic metal strip involved in this embodiment will be described below.
[0067] M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn and V.
[0068] The content of M (a) satisfies 0 ≤ a ≤ 0.100. That is, it can also be M-free. It can also be 0.020 ≤ a ≤ 0.080. When a is small, the crystal grain size tends to increase, the coercivity tends to increase, and the permeability μ' tends to decrease. When a is large, the permeability μ' tends to decrease. Herein, permeability μ' refers to the real part of the complex permeability. Hereafter, permeability μ' is sometimes simply referred to as permeability.
[0069] The content of B (b) satisfies 0.020 ≤ b ≤ 0.200. It can also be 0.025 ≤ b ≤ 0.200, 0.060 ≤ b ≤ 0.180, or 0.080 ≤ b ≤ 0.180. When b is smaller, the crystal grain size (described later) tends to increase, the coercivity tends to increase, and the permeability tends to decrease. When b is larger, the permeability tends to decrease.
[0070] The phosphorus content (c) satisfies 0 ≤ c ≤ 0.100. That is, it can also be free of phosphorus. Alternatively, it can be 0.001 ≤ c ≤ 0.100, or 0.003 ≤ c ≤ 0.100. By keeping the phosphorus content within these ranges, coercivity tends to decrease, and permeability tends to increase. When c is too large, coercivity tends to increase, and permeability tends to decrease.
[0071] The Si content (d) satisfies 0 ≤ d < 0.160. That is, it can also be Si-free. Alternatively, it can be 0 ≤ d ≤ 0.150 or 0 ≤ d ≤ 0.100. When d is larger, the coercivity tends to increase and the permeability tends to decrease.
[0072] The C content (e) satisfies 0 ≤ e ≤ 0.030. That is, it can also be C-free. Alternatively, it can be 0 ≤ e ≤ 0.025 or 0 ≤ e ≤ 0.020. When e is larger, the coercivity tends to increase and the permeability tends to decrease.
[0073] X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements. The content (f) of X2 satisfies 0 ≤ f ≤ 0.030. That is, it is also possible to have no X2.
[0074] X1 can be one or more selected from Co and Ni. p can also be 0, meaning it can be devoid of X1. Furthermore, p can be considered the substitution ratio when X1 replaces a portion of Fe. It can also be 0 ≤ p ≤ 0.500.
[0075] There is no particular restriction on the total content of Fe and X1 (selected from one or more of Co and Ni) (1 - (a + b + c + d + e + f)), which can be 0.720 ≤ (1 - (a + b + c + d + e + f)) ≤ 0.920. By keeping 1 - (a + b + c + d + e + f) within the above range, it is less likely to form a crystalline phase with an average crystal grain size greater than 50 nm. Furthermore, in the following description, Z is set to 1 - (a + b + c + d + e + f).
[0076] Furthermore, the soft magnetic metal strip involved in this embodiment may also contain elements other than those mentioned above, that is, elements other than Fe, X1, X2, M, B, P, Si, and C as unavoidable impurities. For example, it may contain 0.5% by weight or less relative to 100% by weight of the soft magnetic metal strip.
[0077] The soft magnetic metal strip involved in this embodiment includes an amorphous portion and a crystalline portion. The term "soft magnetic metal strip including an amorphous portion and a crystalline portion" means that the amorphization rate X, as shown below, is greater than 0% and less than 100%.
[0078] The amorphization rate X can be determined by X-ray crystal structure analysis using XRD, or by EBSD (crystal orientation analysis) or electron beam diffraction. The method of determining it using XRD-based crystal structure analysis is described below.
[0079] The amorphization rate X of soft magnetic metal powder is represented by the following formula (1).
[0080]
[0081] Ic: Integral intensity of crystalline scattering
[0082] Ia: Integral intensity of amorphous scattering
[0083] Regarding the amorphization rate X, XRD is used to perform X-ray crystal structure analysis on soft magnetic metal thin strips to identify the phases. The peaks of crystallized Fe or compounds (Ic: integrated intensity of crystalline scattering, Ia: integrated intensity of amorphous scattering) are read, and the crystallization rate is calculated from the peak intensity using the above formula (1). The calculation method will be explained in more detail below.
[0084] XRD was used to analyze the crystal structure of soft magnetic metal thin strips. The obtained graphs were profiled using the Lorentz function of equation (2). Then, a crystal composition pattern α representing the crystalline scattering integral intensity was obtained. c α represents the amorphous composition pattern representing the integral intensity of amorphous scattering. a , and the pattern α formed by combining them c+a Based on the crystalline scattering integral intensity and amorphous scattering integral intensity of the obtained pattern, the amorphization rate X is calculated using the above equation (1). The measurement range for calculating the amorphization rate X is set to the range where the diffraction angle 2θ = 30° to 60° from the amorphous halo can be confirmed. Within this range, the error between the measured integral intensity obtained by XRD and the integral intensity calculated using the Lorentz function is within 1%.
[0085]
[0086] h: Peak height
[0087] u: Peak position
[0088] w: Half-peak width
[0089] b: Background height
[0090] Soft magnetic metal ribbons can contain Fe-based nanocrystals with an average grain size of less than 50 nm. Fe-based nanocrystals are nanocrystals with Fe as the main component. Fe-based nanocrystals can also be α-Fe nanocrystals. These α-Fe nanocrystals may contain dissolved Co and / or Ni. They may also contain other constituent elements such as Si. The crystal structure of Fe-based nanocrystals is bcc (body-centered cubic lattice structure).
[0091] One of the main surfaces of the soft magnetic metal strip is designated as the first surface. The surface located opposite the first surface is designated as the second surface.
[0092] Regarding the angles of the X-ray diffraction peaks from Fe-containing crystals in the first and second surfaces of the soft magnetic metal ribbon, the angles are obtained by contour fitting using the Lorentz function of equation (2) above, for a graph obtained by setting the measurement range to 2θ = 30° to 70°.
[0093] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization in the first plane of the soft magnetic metal ribbon is denoted as 2θ1, and the crystal plane indices are set to (h1, k1, l1), the condition 60.00° ≤ 2θ1 ≤ 66.00° is satisfied. When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization in the second plane of the soft magnetic metal ribbon located opposite the first plane is denoted as 2θ2, and the crystal plane indices are set to (h2, k2, l2), the condition 60.00° ≤ 2θ2 ≤ 66.00° is satisfied. Furthermore, 2θ1 - 2θ2 = Δθ 12 When 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
[0094] Existing soft magnetic metal ribbons have identical compositions on both the first and second surfaces, with the same crystal structure on both surfaces. Furthermore, the X-ray diffraction peaks measured on the first and second surfaces have the same positions. That is, by selecting peaks with identical crystal plane indices on both surfaces and setting the angles of each peak to 2θ1 and 2θ2, 2θ1 = 2θ2 is satisfied. Moreover, it was previously believed that the soft magnetic metal ribbon as a whole could have a uniform structure; therefore, it was assumed that 2θ1 = 2θ2 would also be satisfied in all X-ray diffraction peaks.
[0095] The surface roughness of the first surface of the soft magnetic metal strip involved in this embodiment is different from that of the second surface. As a result, the positions of the atoms constituting the unit cells in the crystals contained in the first surface and the crystals contained in the second surface are different. Therefore, let 2θ1-2θ2=Δθ 12 At that time, there exists a condition that satisfies 0.00° < |Δθ 12| X-ray diffraction peak ≤ 4.90°.
[0096] Satisfying 0.00° < |Δθ 12 | Soft magnetic metal strips with an angle ≤4.90° and existing Δθ 12 Compared to soft magnetic metal strips with a coefficient of 0, stress is more easily mitigated. As a result, magnetic properties are more easily improved, particularly coercivity, which decreases and permeability, which increases.
[0097] It can also satisfy 0.00°<|Δθ 12 | ≤1.00° can also satisfy 0.00°<|Δθ 12 | ≤0.50°.
[0098] Especially when performing XRD measurements on soft magnetic metal ribbons containing Fe-based nanocrystals, large X-ray diffraction peaks from these crystals tend to appear around 45° and 65°. For example, when indexed with bcc-Fe, the crystal plane index of the X-ray diffraction peak appearing around 45° is (110), and the crystal plane index of the X-ray diffraction peak appearing around 65° is (200).
[0099] When XRD is performed in the range of 2θ = 30° to 90°, a relatively large X-ray diffraction peak from Fe-based nanocrystals also appears near 2θ = 82°. For example, when indexed using bcc-Fe, the crystal plane index of the X-ray diffraction peak near 82° is (211).
[0100] There is no particular limitation on the height of X-ray diffraction peaks with angles of 2θ1 and 2θ2. When XRD measurements are performed in the range of 2θ = 30° to 90°, the peak intensity ratio relative to the highest X-ray diffraction peak can be more than 1 / 20.
[0101] The magnetic core 1 according to this embodiment is formed by winding a thin strip of soft magnetic metal according to this embodiment. The wound magnetic core 1 according to this embodiment only needs to have a wound portion with the thin strip of soft magnetic metal wound around it. Examples of the shape of the magnetic core 1 include... Figure 1 The ring shape shown Figure 2 The rounded quadrilateral shape shown Figure 3 The elliptical shape shown, etc. Figures 1-3 The shape shown is an example of the shape of the magnetic core 1 according to this embodiment. The shape of the magnetic core 1 can be arbitrary depending on the application and implementation conditions.
[0102] The magnetic core 1 may also have a hollow portion where the soft magnetic metal strip is not present at the center. The area surrounded by the soft magnetic metal strip is called the hollow portion. The hollow portion may also be a gap. Components other than the soft magnetic metal strip can be placed in the hollow portion. For example, busbars, coils, mounting boxes, resin, etc., can be placed there.
[0103] The magnetic core 1 can have multiple generally straight edges. These generally straight edges can be opposite each other or not. The lengths of these generally straight edges can be equal or different. By utilizing the shape of these edges, it is possible to exhibit an elliptical shape or a triangular shape, etc., that includes the generally straight edges.
[0104] Regarding the outer dimension of the magnetic core 1 with approximately straight sides, the length of the side of the circumscribed right-angled quadrilateral with the smallest area among those that encompass the entire outer perimeter is taken as the outer dimension. When multiple circumscribed right-angled quadrilaterals with the smallest area exist, any one of these multiple circumscribed right-angled quadrilaterals can be selected.
[0105] Regarding the inner dimensions of the magnetic core 1 with approximately straight sides, the length of the side of the circumscribed right quadrilateral with the smallest area encompassing the entire hollow portion (the interior of the inner periphery) can be used. If multiple corresponding quadrilaterals exist, any one can be chosen.
[0106] Choose two orthogonal sides from the four sides of the circumscribed right quadrilateral with the smallest area encompassing the entire perimeter. Let the lengths of these two orthogonal sides be Loa and Lob (Loa ≤ Lob). In this case, 1 ≤ Lob / Loa ≤ 10. When calculating Lob / Loa, round the first decimal place.
[0107] Choose two orthogonal sides from the four sides of the circumscribed right quadrilateral containing the smallest area of the entire hollow portion. Let the lengths of these two orthogonal sides be Lia and Lib (Lia ≤ Lib). In this case, 1 ≤ Lib / Lia ≤ 20. When calculating Lib / Lia, round the first decimal place.
[0108] The magnetic core 1 in this embodiment is formed by stacking the soft magnetic metal strips involved in this embodiment. The magnetic core 1 in this embodiment only needs to have a stacked portion with the soft magnetic metal strips stacked on it.
[0109] The following describes the manufacturing method of the soft magnetic metal strip according to this embodiment.
[0110] There are no particular limitations on the manufacturing method of soft magnetic metal strips. For example, there is a method that uses a single roll to manufacture soft magnetic metal strips. In addition, the strip can also be a continuous strip.
[0111] In the single-roller process, firstly, pure metals, alloys containing the respective metal elements, and / or compounds containing the respective metal elements are prepared as raw materials and weighed in a manner that ensures the same composition as the final soft magnetic metal strip. Then, the weighed raw materials are melted and mixed to create a master alloy. The melting method for the raw materials is not particularly limited; for example, it can be achieved by melting the materials under high-frequency heating after evacuating the chamber. Furthermore, the master alloy typically has the same composition as the final soft magnetic metal strip.
[0112] Next, the prepared master alloy is heated to melt it, resulting in molten metal (liquid). There are no particular restrictions on the temperature of the molten metal; for example, it can be 1200–1600°C.
[0113] A schematic diagram of the apparatus used in the single-roller method according to this embodiment is shown below. Figure 4 In the single-roller method according to this embodiment, molten metal 32 is injected and supplied from nozzle 31 into roller 33, which rotates in the direction of the arrow, inside chamber 35, thereby producing a soft magnetic metal strip 34 along the rotation direction of roller 33. The material of roller 33 is not particularly limited. For example, a roller made of Cu can be used. The temperature of roller 33 is also not particularly limited. For example, it can be 20°C to 80°C.
[0114] In the main surface of the soft magnetic metal strip 34, the surface that does not contact the roller 33 is designated as the free surface 34a, and the surface that contacts the roller 33 is designated as the roller surface 34b.
[0115] The thickness of the soft magnetic metal strip 34 can be adjusted by changing the rotation speed of the roller 33, the distance between the nozzle 31 and the roller 33, and the temperature of the molten metal. There are no particular limitations on the thickness of the soft magnetic metal strip 34. For example, it can be set from 5 μm to 200 μm.
[0116] The width of the soft magnetic metal strip 34 can be adjusted by adjusting the opening of the nozzle 31, the temperature of the molten metal, etc. There is no particular limitation on the width of the soft magnetic metal strip 34. For example, it can be set from 5mm to 200mm.
[0117] There are no particular limitations on the vapor pressure inside chamber 35. For example, Ar gas with dew point adjusted can be used to make the vapor pressure inside chamber 35 below 1 hPa. Alternatively, chamber 35 can be omitted. That is, the vapor pressure in the atmosphere in which the single-roller process is performed can also be equal to the vapor pressure in the atmosphere.
[0118] The soft magnetic metal ribbon 34, obtained by cooling molten metal using a single-roller method, can possess a nano-heterogeneous structure with initial microcrystals within an amorphous state. Upon undergoing the heat treatment described later, Fe-based nanocrystals readily precipitate from the soft magnetic metal ribbon 34. The average grain size of the initial microcrystals is not particularly limited; for example, it can be 0.5 nm to 3 nm.
[0119] Furthermore, there are no particular limitations on the methods for observing the presence or absence of initial microcrystals and the average crystal size. For example, for samples that have been thinned using ion milling, confirmation can be made by using a transmission electron microscope to obtain confined field diffraction images, nanobeam diffraction images, bright field images, or high-resolution images. When using confined field diffraction images or nanobeam diffraction images, in the diffraction pattern, amorphous materials form ring-shaped diffraction patterns, while non-amorphous materials form diffraction spots due to the crystalline structure. Additionally, when using bright field images or high-resolution images, at a magnification of 1.00 × 10⁻⁶... 5 ~3.00×10 5 By visual inspection, the presence or absence of initial microcrystals and the average crystal grain size can be observed.
[0120] There are no particular restrictions on the temperature, rotational speed of roller 33, or the atmosphere inside chamber 35. For amorphization, the temperature of roller 33 can be set to 4–50°C. There is a tendency that the faster the rotational speed of roller 33, the smaller the average grain size of the initial microcrystals. Considering cost, the atmosphere inside chamber 35 can be set to atmospheric pressure.
[0121] The following describes a method for manufacturing a soft magnetic metal ribbon with an Fe-based nanocrystalline structure by heat treatment of amorphous soft magnetic metal ribbons.
[0122] There are no particular limitations on the heat treatment conditions used to manufacture the soft magnetic metal strip involved in this embodiment. The possible heat treatment conditions vary depending on the composition of the soft magnetic metal strip. Typically, the possible heat treatment temperature is approximately 450–650°C, and the possible heat treatment time is approximately 0.5–10 hours. However, depending on the composition, there are sometimes possible heat treatment temperatures and times outside the above ranges. Furthermore, there are no particular limitations on the atmosphere used during heat treatment. It can be carried out in a reactive atmosphere such as air or in a non-reactive atmosphere such as Ar gas.
[0123] Furthermore, there are no particular limitations on the method for calculating the average grain size of Fe-based nanocrystals contained in the soft magnetic metal ribbons obtained through heat treatment. For example, a method can be described that measures the diameter of cross-sections of multiple Fe-based nanocrystals and averages the results. First, a bright-field image of the cross-section of the soft magnetic metal ribbon, which has been thinned using ion milling, is obtained. For example, a transmission electron microscope can be used at a magnification of 1×10⁻⁶. 5 Times ~ 1×10 6 By observing the cross-section of the thinned sample, a bright-field image can be obtained. The obtained bright-field image contains grain images of multiple Fe-based nanocrystals. For these grain images, the diameter is measured and the average value is calculated, thereby allowing the calculation of the average crystal grain size of the Fe-based nanocrystals.
[0124] The number of grain images used for diameter measurement is more than 100.
[0125] The equivalent circle diameter of the grain image can be considered as the diameter of the grain image itself. Specifically, the area of the grain image is calculated based on the number of pixels forming the grain image, and the equivalent circle diameter is calculated based on the area, thus determining the diameter of the grain image. When the grain image is circular, the length of the line segment drawn from a point on the outer periphery of the grain image through the center to a point on the opposite outer periphery can be used as the diameter.
[0126] Furthermore, there are no particular limitations on the methods for confirming that the crystal structure is bcc (body-centered cubic lattice structure). For example, X-ray diffraction can be used for confirmation.
[0127] To manufacture the soft magnetic metal strip 34 according to this embodiment, the free surface 34a and / or the roller surface 34b are ground before the aforementioned heat treatment. Alternatively, only either the free surface 34a or the roller surface 34b may be ground. The grinding method is not particularly limited. For example, a grinding roller formed by winding abrasive paper onto a roller can be used, or a grinding wheel roller with an electrodeposition wheel for electrodepositing diamond powder or CBN powder can be used. The use of a grinding wheel roller will be described below. The grit number of the grinding wheel is not particularly limited. For example, it can be #1600 to #12000.
[0128] The surface that has undergone the above-described grinding process shifts the peak angle in the diffraction chart towards a lower angle. Furthermore, using a grinding wheel with a smaller mesh size results in a greater shift in the peak angle in the diffraction chart. Therefore, by grinding at least one surface of a soft magnetic metal ribbon using a grinding wheel with an appropriate mesh size, it is possible to reduce |Δθ|. 12 | Greater than 0.00°.
[0129] Shrinkage stress is generated on the polished surface of the soft magnetic metal strip 34, while tensile stress is generated on the opposite surface. Therefore, the stress relief effect of the heat treatment following polishing is easily achieved. As a result, the magnetic properties of the soft magnetic metal strip 34 are easily improved.
[0130] Furthermore, the unevenness of the soft magnetic metal strip 34 is reduced due to grinding. As a result, the stacking factor of the magnetic core made using the soft magnetic metal strip 34 can be easily increased, and the magnetic properties can be easily improved.
[0131] However, in |Δθ 12 If the stress difference is too large, the stress difference between the two surfaces of the soft magnetic metal strip 34 becomes excessive. As a result, the magnetic properties of the soft magnetic metal strip 34 decrease, and the magnetic properties of the magnetic core using the soft magnetic metal strip 34 also decrease.
[0132] The following is about Figure 1 The manufacturing method of the annular magnetic core 1 (wound core 1) shown will be described. In the following description, the free surface 34a is sometimes referred to as the first surface and the roller surface 34b as the second surface.
[0133] The magnetic core 1 has a winding portion formed by winding a thin strip of soft magnetic metal. In this embodiment, the entire magnetic core 1 constitutes the winding portion, but it is sufficient if only a portion of the magnetic core 1 includes the winding portion.
[0134] An adhesive layer may be formed on the first and / or second surfaces of the soft magnetic metal strip as needed, or a rust-preventive oil may be applied. As the adhesive layer, known adhesive layers can be used. For example, an adhesive layer formed with an adhesive composed of acrylic resin, silicone resin, butadiene resin, epoxy resin, etc., may be used. An adhesive layer formed with a hot melt may also be used. Double-sided tape containing a PET substrate may also be used as the adhesive layer. As the rust-preventive oil, known rust-preventive oils may be used. For example, petroleum-based solvents may be listed. Furthermore, to the extent that it does not impair the function of the magnetic core 1, the magnetic core 1 (winding section) may also include components other than the soft magnetic metal strip and the adhesive layer. For example, the winding section may include a core. A protective film may be provided on the outer and / or inner peripheral sides of the winding section. As the protective film, known protective films may be used. For example, PET film, polyimide film, aramid film, etc., may be listed. Alternatively, the winding section may be placed in a protective box made of resin or ceramic, etc.
[0135] There are no particular restrictions on the number of turns of the soft magnetic metal strip. For example, it can be between 1 and 15,000.
[0136] It can be designed such that the first surface (free surface) is the outermost surface 11 and the second surface (roller surface) is the innermost surface 13. Conversely, it can also be designed such that the first surface (free surface) is the innermost surface 13 and the second surface (roller surface) is the outermost surface 11.
[0137] The following is about Figure 1 The method for manufacturing the annular magnetic core (layered core) 1 shown is explained.
[0138] The magnetic core 1 has a stacked portion formed by laminating thin strips of soft magnetic metal. In this embodiment, the entire magnetic core 1 constitutes the stacked portion, but it is sufficient if only a portion of the magnetic core 1 includes the stacked portion.
[0139] An adhesive layer may be formed on the first and / or second surfaces of the soft magnetic metal strip as needed. Alternatively, the adhesive layer may be formed on a polished surface or an unpolished surface. The type of adhesive layer is the same as that of the adhesive layer in the wound core 1. Furthermore, without impairing the function of the magnetic core 1, the magnetic core 1 (stacked portion) may also include constituent elements other than the soft magnetic metal strip and the adhesive layer. Figure 1 The upper and / or lower surfaces of the laminated core 1 (laminated portion) shown may have a protective film. Known protective films can be used as the protective film. Examples include PET film, polyimide film, and aramid film. Alternatively, the laminated portion may be placed in a protective box made of resin or ceramic.
[0140] There are no particular restrictions on the number of layers in the soft magnetic metal strip. For example, it can be more than 4 layers but less than 25,000 layers.
[0141] There are no particular restrictions on the orientation of the soft magnetic metal strips used to fabricate the laminated sections. For example, they can be laminated with the first side (free side) of one soft magnetic metal strip and the second side (roller side) of another soft magnetic metal strip in contact with each other, or they can be laminated face-to-face with an adhesive layer in between. Furthermore, along the lamination direction, the two outer sides can also be a combination of the first and second sides.
[0142] In addition, along the lamination direction, both of the two outer surfaces can be first surfaces (free surfaces), and both of the two outer surfaces can be second surfaces (roller surfaces). That is, the magnetic core 1 can include portions where the first surfaces and / or the second surfaces are in contact with each other, and portions where the first surfaces and / or the second surfaces are face-to-face with each other separated by an adhesive layer.
[0143] The magnetic component according to this embodiment includes the aforementioned soft magnetic metal strip. Furthermore, the magnetic component according to this embodiment includes the aforementioned magnetic core. The application of the magnetic component is not particularly limited. It can be applied to applications requiring low power consumption and high efficiency. For example, it can be used in transformers, reactors, choke coils, noise suppression components, etc.
[0144] (Second Implementation)
[0145] The following uses Figure 1 The magnetic core involved in the second embodiment will be described, but the parts not specifically described are the same as those in the first embodiment.
[0146] The magnetic core involved in this embodiment is a magnetic core having a wound portion with a soft magnetic metal strip wound around it, the soft magnetic metal strip having a composition of (Fe 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The principal components are shown in the (atomic ratio)
[0147] X1 is selected from one or more of Co and Ni.
[0148] X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements.
[0149] M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V.
[0150] It satisfies 0≤a≤0.100, 0.020≤b≤0.200, 0≤c≤0.100, 0≤d<0.160, 0≤e≤0.030, 0≤f≤0.030, and 0≤p≤0.500.
[0151] That is, the magnetic core (wound core) according to the second embodiment has the same composition as the soft magnetic metal strip according to the first embodiment. The winding portion, including the amorphous portion and the crystalline portion, is also the same as that of the wound core obtained by winding the soft magnetic metal strip according to the first embodiment.
[0152] The magnetic core involved in this embodiment may have a winding portion formed by winding a thin strip of soft magnetic metal. Figures 1-3The magnetic core 1 shown is entirely a wound section. Furthermore, when the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the outer surface of the soft magnetic metal strip located on the outermost surface 11 of the wound section (magnetic core 1) is set to 2θ3, and the crystal plane indices are set to (h3, k3, l3), the following conditions are met: 60.00° ≤ 2θ3 ≤ 66.00°.
[0153] When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the inner surface of the soft magnetic metal strip located on the innermost surface 13 of the winding section (magnetic core 1) is set to 2θ4, and the crystal plane indices are set to (h4, k4, l4), the following conditions are met: 60.00°≤2θ4≤66.00°.
[0154] Let it be 2θ3-2θ4=Δθ 34 hour,
[0155] Satisfying 0.00° < |Δθ 34 | ≤4.90° and (h3, k3, l3) = (h4, k4, l4).
[0156] The measurement site for determining the X-ray diffraction peak of θ3 can be any part of the outermost surface 11 of the winding portion. Alternatively, sampling can be performed at any location including the outermost surface 11, and the X-ray diffraction peak of the resulting sample can be measured. The measurement site for determining the X-ray diffraction peak of θ4 can be any part of the innermost surface 13 of the winding portion. Alternatively, sampling can be performed at any location including the innermost surface 13, and the X-ray diffraction peak of the resulting sample can be measured.
[0157] Satisfying 0.00° < |Δθ 34 | ≤4.90° magnetic core and Δθ 34 Compared to a core with a 0.00° angle, stress is more easily mitigated. As a result, magnetic properties are more easily improved. In particular, coercivity decreases and permeability increases.
[0158] It can also satisfy 0.00°<|Δθ 34 | ≤1.00° can also satisfy 0.00°<|Δθ 34 | ≤0.50°.
[0159] The magnetic core 1 according to this embodiment may have a winding portion formed by winding the soft magnetic metal strip according to the first embodiment. That is, the soft magnetic metal strip used to manufacture the magnetic core 1 according to this embodiment may have the same composition as the soft magnetic metal strip according to the first embodiment. The soft magnetic metal strip used to manufacture the magnetic core 1 according to this embodiment may also include an amorphous portion and a crystalline portion, just like the soft magnetic metal strip according to the first embodiment. Furthermore, the soft magnetic metal strip used to fabricate the magnetic core 1 according to this embodiment can also be a soft magnetic metal strip as follows: when the angle of one peak selected from the X-ray diffraction peaks from the crystal in the first surface is set as 2θ1, and the crystal plane index is set as (h1, k1, l1), 2θ1 satisfies 60.00°≤2θ1≤66.00°; when the angle of one peak selected from the X-ray diffraction peaks from the crystal in the second surface located on the opposite side of the first surface is set as 2θ2, and the crystal plane index is set as (h2, k2, l2), 2θ2 satisfies 60.00°≤2θ2≤66.00°, and is set as 2θ1-2θ2=Δθ 12 When 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
[0160] The inner circumferential shape of the wound portion in a cross-section perpendicular to the winding axis can be a shape having two or more curvature circles with centers different from each other. A curvature circle is a circle used to determine the value of the curvature of a local portion contained within a curved section, i.e., the radius of curvature R. If the shape of the local portion is an arc, then the circle containing the arc is the curvature circle, and the geometric radius of the arc (the radius of the curvature circle) is the radius of curvature R. If the shape of the local portion is not an arc, then an arc with a shape closest to the shape of the local portion is fitted. In the fitting, for example, the circle with the largest overlap with the local portion can be used as the curvature circle. The geometric radius of the arc (the radius of the curvature circle) is the radius of curvature R. Furthermore, curvature circles with a length less than 100 μm or a radius less than 50 μm are not considered.
[0161] The radii of two or more of the aforementioned curvature circles in a section perpendicular to the winding axis may be smaller than the equivalent circle diameter of the hollow portion of the winding section.
[0162] The outer periphery of the winding portion in a cross-section perpendicular to the winding axis has the shape of two or more curvature circles with different centers, and the radius of the two or more curvature circles is smaller than the equivalent circle diameter of the hollow portion of the winding portion. An example can be given. Figure 2 The examples shown include a rounded quadrilateral shape with four corners and four straight sections, and a rounded triangle shape with three corners and three straight sections. Figure 3 The elliptical shape shown has two corners and a straight section.
[0163] The inner circumference length of the winding core, that is, the line where the distance between the outer and inner circumference surfaces of the winding core is equal. Figures 1-3 The length of the line shown by the dashed line is not particularly limited. For example, it can be between 1 mm and 1000 mm. In addition, the inner circumference length can be measured directly or calculated based on the radius of curvature R of the curvature circle and the approximate length of the straight line.
[0164] The manufacturing method of the magnetic core 1 in this embodiment is the same as the manufacturing method of the wound core 1 in the first embodiment.
[0165] Example
[0166] (Experimental Example 1)
[0167] <Fabrication of Soft Magnetic Strips>
[0168] In samples numbered 1-1 to 1-33, the raw material metal was weighed to ensure that the alloy composition, based on the atomic ratio, was Fe. 0.820 Nb 0.060 B 0.090 P 0.030 The metal was melted by high-frequency heating to produce a master alloy. In samples 2-1 to 2-33, the raw material metal was weighed to ensure the alloy composition, based on atomic ratio, was Fe. 0.735 Nb 0.030 B 0.090 Si 0.135 Cu 0.010 The master alloy is produced by melting it through high-frequency heating.
[0169] Next, the prepared master alloy is heated to melt it, and after being made into a molten metal, it is used... Figure 4 The apparatus shown uses a single-roller method to produce a thin strip. The atmosphere inside the chamber is set to atmospheric. The thickness of the thin strip is approximately 20 μm. The width of the thin strip is 10 mm, the same as the height of the winding section described later.
[0170] Next, in each embodiment, one side of the strip is ground using a grinding wheel. The grinding conditions are controlled according to the mesh size of the grinding wheel, and the grinding amount is adjusted to adjust the strip thickness. Specifically, the thickness of the ground strip is 20 μm. The ground surface and the mesh size of the grinding wheel are shown in Tables 1A and 1B.
[0171] The thin strip was then subjected to heat treatment. The heat treatment conditions were 575℃ and 60 minutes.
[0172] <Magnetic Properties of Soft Magnetic Strips>
[0173] The coercivity of the soft magnetic strip was measured using an HC meter (K-HC1000 manufactured by Tohoku Special Steel Co., Ltd.). Permeability was measured at a frequency of 1 kHz using a BH analyzer (SY-8218, Iwasaki Telecommunications Co., Ltd.) and a small single-plate magnetic measuring device (SY-956, Iwasaki Telecommunications Co., Ltd.). Furthermore, the improvement rates of coercivity and permeability were calculated based on samples subjected to the same conditions (excluding grinding). The results are shown in Tables 1A and 1B. Regarding the evaluation, cases where the improvement rate of coercivity and / or permeability is less than 5% are designated as D. Cases where the improvement rate of coercivity and permeability is 5% or more but less than 10% are designated as C. Cases where the improvement rate of coercivity and permeability is 10% or more but less than 20% are designated as B. Cases where the improvement rate of coercivity and the improvement rate of permeability are 20% or more are designated as A. The soft magnetic strips of each embodiment and comparative example exhibit excellent magnetic properties in the order of A, B, C, and D, while the magnetic properties are suitable in cases A to C.
[0174] <Microstructure of soft magnetic ribbons>
[0175] The fine structure of the free and roll surfaces of each heat-treated ribbon was confirmed by X-ray diffraction (XRD). The results confirmed that all ribbons contained Fe-based nanocrystalline and amorphous portions in both the free and roll surfaces. Furthermore, the average grain size of the Fe-based nanocrystals in each surface was confirmed; for ribbons of the same size, the average grain size of the Fe-based nanocrystals was identical in both the free and roll surfaces. The results are shown in Tables 1A and 1B.
[0176] In addition, for each heat-treated ribbon, diffraction charts were prepared and analyzed for both the roller surface and the free surface within the range of 2θ = 30° to 70°. In all samples, one large peak from the Fe-based nanocrystals appeared near 2θ = 45° and another near 2θ = 65°. The peak angles of the diffraction peaks near 65° in the diffraction charts for each surface were specified, and the angle differences were calculated. The results are shown in Tables 1A and 1B. In all diffraction charts, the large peaks near 45° all have the same crystal plane indices. In all diffraction charts, the large peaks near 65° all have the same crystal plane indices.
[0177] [Table 1A]
[0178]
[0179] [Table 1B]
[0180]
[0181] According to Tables 1A and 1B, the embodiments in which a surface was ground using a grinding wheel with a mesh size of 1600 or higher exhibited better magnetic properties compared to the comparative examples where all other conditions were the same except for no grinding. In contrast, the comparative examples in which a surface was ground using a grinding wheel with a mesh size of 1500 exhibited worse magnetic properties compared to the comparative examples where all other conditions were the same except for no grinding. This is likely because the mesh size of the grinding wheel was too small, resulting in an excessively large angular difference in the diffraction patterns of each surface.
[0182] (Experimental Example 2)
[0183] For test samples 1-1 and 1-8 of Experimental Example 1, the experiments were conducted under the same conditions, except for changes in composition. The results are shown in Tables 2 to 8. Hereafter, in the tables up to Table 9, |Δθ| near 65° is omitted. 12 Data on the angles of diffraction peaks other than |.
[0184] [Table 2A]
[0185]
[0186] [Table 2B]
[0187]
[0188] [Table 2C]
[0189]
[0190] [Table 2D]
[0191]
[0192] [Table 3A]
[0193]
[0194] [Table 3B]
[0195]
[0196] [Table 3C]
[0197]
[0198] [Table 3D]
[0199]
[0200] [Table 3E]
[0201]
[0202] [Table 4]
[0203]
[0204] [Table 5]
[0205]
[0206] [Table 6]
[0207]
[0208] [Table 7]
[0209]
[0210] [Table 8A]
[0211]
[0212] [Table 8B]
[0213]
[0214] [Table 8C]
[0215]
[0216] [Table 8D]
[0217]
[0218] According to Tables 2 to 8, when the composition of the soft magnetic metal strip is within a specific range, the embodiments in which one surface is ground using a grinding wheel with a mesh size of 1600 or higher exhibit better magnetic properties compared to the comparative examples where all other conditions are the same except for no grinding. In contrast, when the composition is outside the specific range, the magnetic properties are not sufficiently improved even with grinding.
[0219] (Experimental Example 3)
[0220] For samples 6-1 and 6-2, the average crystal size of the Fe-based nanocrystals was varied by changing the heat treatment temperature and / or heat treatment time, otherwise the same conditions were applied. The results are shown in Table 9.
[0221] [Table 9]
[0222]
[0223] According to Table 9, the magnetic properties are preferred even when the average crystal grain size of the Fe-based nanocrystals is changed. Furthermore, the magnetic properties are particularly preferred when the average crystal grain size of the Fe-based nanocrystals is 50.0 nm or less.
[0224] (Experimental Example 4)
[0225] In Experiment 1, a soft magnetic metal strip with its free surface ground was used to make a winding core.
[0226] The soft magnetic metal strip is wound in such a way that the outermost surface, i.e., the outermost circumference of the winding portion, becomes the surface shown in the table, to create the soft magnetic metal strip. Figure 1 The shown is a ring-shaped winding core. Specifically, winding is performed with the side not shown in the table (the side described as a free side in the table is the roller side, and vice versa) as the inner side. Furthermore, the heat treatment of the soft magnetic metal strip is performed after winding.
[0227] The dimensions of the winding core are shown in the table. In particular, the size of the winding core is controlled so that the inner diameter is the value shown in the table. The number of windings of the winding core is controlled so that the outer diameter is the value shown in the table. The winding core is removed after winding. In addition, when the number of windings of the soft magnetic metal strip is set to N1, the thickness of the soft magnetic metal strip is set to t, the inner diameter of the winding part is set to ID, and the outer diameter of the winding part is set to OD, the stacking factor of the winding core at any measurement location is expressed by the following formula (3). For one winding core, four or more of the above measurement locations are set, the stacking factor is measured at each measurement location, the obtained stacking factors are averaged, and the stacking factor of the entire winding core is calculated. In this experimental example, the stacking factor is 80% in all winding cores.
[0228]
[0229] The coercivity of the wound core was measured using an HC meter (K-HC1000 manufactured by Tohoku Special Steel Co., Ltd.). The inductance of the wound core was measured at a frequency of 1 kHz using an LCR meter (4284A manufactured by Agilent Technologies Inc.) by winding polyurethane copper wire (UEW wire) onto the wound core. The permeability of the wound core was calculated based on the inductance of the wound core. The results are shown in Table 10.
[0230] Using samples taken from the region containing the outermost surface and samples taken from the region containing the innermost surface, the XRD diffraction pattern of the wound core was obtained using the same method as that used for the XRD diffraction pattern of the thin strip.
[0231] [Table 10]
[0232]
[0233] According to Table 10, the wound cores of each embodiment, in which the angle difference of the diffraction chart between the outermost and innermost surfaces is within a specified range by winding the soft magnetic metal strip of the embodiment, have better magnetic properties than the wound cores of each comparative example, in which the angle difference of the diffraction chart between the outermost and innermost surfaces is outside a specified range by winding the soft magnetic metal strip of the comparative example.
[0234] (Experimental Example 5)
[0235] Using soft magnetic metal strips numbered 1-1 and 1-8, a stacked core with the same dimensions as samples numbered 201, 208, 234, and 235 in Experimental Example 4 was fabricated.
[0236] First, the polished soft magnetic metal strip is stamped into an annular shape with the outer and inner diameters shown in the table, and then heat-treated. Next, double-sided adhesive tape containing a PET substrate with a 5μm thick adhesive layer is adhered to one side of the soft magnetic metal strip. Then, the PET substrate is peeled off, forming the adhesive layer on one side of the soft magnetic metal strip. The soft magnetic metal strip is then stacked to the height shown in the table using this adhesive layer.
[0237] When the number of layers of the soft magnetic metal strip is set to N2, the thickness of the soft magnetic metal strip is set to t, and the height of the stacked core is set to T, the stacking factor of the stacked core at any measurement location is expressed by the following equation (4). For one stacked core, four or more of the above measurement locations are set, and the stacking factor is measured at each measurement location. The obtained stacking factors are averaged, and the overall stacking factor of the stacked core is calculated from this average. In this experimental example, the stacking factor is 80% in all stacked cores.
[0238]
[0239] The characteristics of the laminated core were measured in the same manner as those of the wound core. The results are shown in Table 11.
[0240] [Table 11]
[0241]
[0242] According to Table 11, the magnetic properties of the stacked cores of each embodiment obtained by stacking the soft magnetic metal strips of the embodiments are better than those of the stacked cores of each comparative example obtained by stacking the soft magnetic metal strips of the comparative examples.
[0243] (Experimental Example 6)
[0244] Alternatively, change the width to 22 mm, and then prepare a soft magnetic metal strip in the same manner as the soft magnetic metal strip of sample number 1-1. Use the obtained soft magnetic metal strip to make a winding core. Or, change the width to 22 mm, grind the free surface, and then prepare a soft magnetic metal strip in the same manner as the soft magnetic metal strip of sample number 1-8. Use the obtained soft magnetic metal strip to make a winding core.
[0245] The soft magnetic metal strip is wound around a roller surface using the outermost surface, i.e., the outermost circumference of the winding section, as the roller surface to produce the product. Figure 3 The elliptical winding core shown has two circles of curvature, and Figure 2 The shown is a wound core with a rounded quadrilateral shape having four circles of curvature. At this point, winding is performed with the free surface as the inside. Furthermore, the heat treatment of the soft magnetic metal strip is performed after winding.
[0246] The dimensions of the winding core are shown in the table. The size of the winding core is controlled so that Lia and Lib are the values shown in the table. The number of windings is controlled so that Loa and Lob are the values shown in the table. The winding core is removed after winding. When the number of windings of the soft magnetic metal strip is set to N1, the thickness of the soft magnetic metal strip is set to t, and the length from the outermost surface to the innermost surface of the winding portion is set to D, the stacking factor of the winding core at any measurement location is expressed by the following equation (5). For one winding core, four or more of the above measurement locations are set, the stacking factor is measured at each measurement location, the obtained stacking factors are averaged, and the overall stacking factor of the winding core is calculated. In this experimental example, the stacking factor is 80% in all winding cores.
[0247]
[0248] The characteristics of the winding core in this experimental example were measured in the same manner as those of the winding core in Experimental Example 4. The results are shown in Table 12.
[0249] [Table 12]
[0250]
[0251] According to Table 12, the wound cores of each embodiment obtained by winding the soft magnetic metal strip of the embodiment have better magnetic properties than the wound cores of each comparative example obtained by winding the soft magnetic metal strip of the comparative example.
[0252] (Experimental Example 7)
[0253] Except for the size of the winding core, the winding core was manufactured in the same manner as specimens 413 and 414 of Experimental Example 6. In specimens 409 to 416 of Experimental Example 6, the size of the winding core was changed in a fixed manner with Lob / Loa and Lib / Lia, but in Experimental Example 7, Lob / Loa and Lib / Lia were changed. The results are shown in Table 13.
[0254] [Table 13]
[0255]
[0256] According to Table 13, the wound cores of each embodiment obtained by winding the soft magnetic metal strip of the embodiment have better magnetic properties than the wound cores of each comparative example obtained by winding the soft magnetic metal strip of the comparative example, even if Lib / Lia and Lob / Loa are specifically changed.
[0257] (Experimental Example 8)
[0258] The line that makes the inner circumference length of the winding core equal to the distance between the outer and inner circumference surfaces of the winding core. Figures 1-3 Based on the premise that the lengths of the lines (shown by the dashed lines) are equal, the number of curvature circles is varied. Otherwise, samples 427 to 432 are prepared under the same conditions as samples 419 and 420. Furthermore, based on the premise that the inner circumference lengths of the winding core are equal, the number of curvature circles is varied. Otherwise, samples 433 to 438 are prepared under the same conditions as samples 405 and 406.
[0259] The shape with one circle of curvature is Figure 1 The shape shown is an annular shape. The shape with two circles of curvature is... Figure 3 The shape shown is an ellipse. A shape with three curvature circles is a rounded triangle. A shape with four curvature circles is... Figure 2 The rounded quadrilateral shape shown.
[0260] In Experiment 8, the inner circumference of the center was calculated based on the radius of curvature R of the curvature circle and the length of the approximate straight line.
[0261] The characteristics of the core in this experimental example were measured in the same manner as those of the wound core in Experimental Example 4. The results are shown in Table 14.
[0262] [Table 14]
[0263]
[0264] According to Table 14, the wound cores of each embodiment obtained by winding the soft magnetic metal strip of the embodiment have better magnetic properties than the wound cores of each comparative example obtained by winding the soft magnetic metal strip of the comparative example, even if their shape is changed, especially the number of curvature circles.
Claims
1. A soft magnetic metal strip, wherein, The soft magnetic metal strip has a composition with an atomic ratio of (Fe) 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The principal components shown are X1 is selected from one or more of Co and Ni. X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements. M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V. The following conditions must be met: 0 ≤ a ≤ 0.100, 0.020 ≤ b ≤ 0.200, 0 ≤ c ≤ 0.100, 0 ≤ d < 0.160, 0 ≤ e ≤ 0.030, 0 ≤ f ≤ 0.030, and 0 ≤ p ≤ 0.
500. The soft magnetic metal strip comprises an amorphous portion and a crystalline portion. When the angle of one peak selected from the X-ray diffraction peaks originating from the crystallization in the first plane of the soft magnetic metal ribbon is set as 2θ1, and the crystal plane indices are set as (h1, k1, l1), the following conditions are met: 60.00°≤2θ1≤66.00°. When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization in the second plane located opposite to the first plane of the soft magnetic metal ribbon is set to 2θ2, and the crystal plane indices are set to (h2, k2, l2), the following conditions are met: 60.00°≤2θ2≤66.00°. Let it be 2θ1-2θ2=Δθ 12 hour, Satisfying 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
2. The soft magnetic metal strip as described in claim 1, wherein, It satisfies 0≤d≤0.
150.
3. The soft magnetic metal strip as described in claim 1 or 2, wherein, Fe-based nanocrystals with an average crystal grain size of less than 50.0 nm.
4. A magnetic core, wherein, It has a winding portion having a soft magnetic metal strip wound around it according to any one of claims 1 to 3.
5. A magnetic core, wherein, It has a laminated portion having a soft magnetic metal strip as described in any one of claims 1 to 3.
6. A magnetic core, wherein, The magnetic core has a wound portion with a thin strip of soft magnetic metal wound around it, the thin strip of soft magnetic metal having a composition in terms of atomic ratio (Fe). 1-p X1 p ) 1-(a+b+c+d+e+f) M a B b P c Si d C e X2 f The principal components shown are X1 is selected from one or more of Co and Ni. X2 is selected from one or more elements including Al, Ag, Zn, Sn, As, Sb, Cu, Cr, Bi, S, O, N, and rare earth elements. M is selected from one or more of Nb, Hf, Zr, Ta, Ti, Mo, W, Mn, and V. The following conditions must be met: 0 ≤ a ≤ 0.100, 0.020 ≤ b ≤ 0.200, 0 ≤ c ≤ 0.100, 0 ≤ d < 0.160, 0 ≤ e ≤ 0.030, 0 ≤ f ≤ 0.030, and 0 ≤ p ≤ 0.
500. The winding portion includes an amorphous portion and a crystalline portion. When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the outer surface of the soft magnetic metal strip located on the outermost surface of the winding portion is set to 2θ3, and the crystal plane indices are set to (h3, k3, l3), the following conditions are met: 60.00°≤2θ3≤66.00°. When the angle of one peak selected from the X-ray diffraction peaks originating from crystallization on the inner surface of the soft magnetic metal strip located on the innermost surface of the winding portion is set to 2θ4, and the crystal plane indices are set to (h4, k4, l4), the following conditions are met: 60.00°≤2θ4≤66.00°. Let it be 2θ3-2θ4=Δθ 34 hour, Satisfying 0.00° < |Δθ 34 | ≤4.90° and (h3, k3, l3) = (h4, k4, l4).
7. The magnetic core as claimed in claim 6, wherein, It satisfies 0≤d≤0.
150.
8. The magnetic core as claimed in claim 6 or 7, wherein, The soft magnetic metal strip comprises an amorphous portion and a crystalline portion. The angle of one peak selected from the X-ray diffraction peaks from the first surface of the soft magnetic metal strip from crystallization is set as 2θ1, and the crystal plane index is set as (h1, k1, l1). The angle of one peak selected from the X-ray diffraction peaks from the crystallization in the second plane located opposite to the first plane of the soft magnetic metal strip is set as 2θ2, and the crystal plane index is set as (h2, k2, l2). Let it be 2θ1-2θ2=Δθ 12 hour, Satisfying 0.00° < |Δθ 12 | ≤4.90° and (h1, k1, l1) = (h2, k2, l2).
9. The magnetic core as claimed in claim 6 or 7, wherein, The winding portion is shaped like two or more curvature circles with different centers.
10. The magnetic core as claimed in claim 9, wherein, The radii of two or more of the curvature circles are smaller than the equivalent circle diameter of the hollow portion of the winding portion.
11. A magnetic component, wherein, A soft magnetic metal strip having any one of claims 1 to 3.
12. A magnetic component, wherein, It has a magnetic core as described in any one of claims 4 to 10.
Citation Information
Patent Citations
Manufacture of hyperfine-crystal soft-magnetic alloy
JP1989247557A